Effect of black tea brew of camellia sinensis on sexual competence of male rats - Ratnasooriya, W.D.; Fernando, T.S.P. (My University, 2008)
In Sri Lankan traditional medicine black tea brew (BTB) of Camellia sinensis (L.) O. Kuntze (Theaceae) is claimed to have male sexual stimulant activity. As this claim is not scientifically tested and proven, this study was undertaken to evaluate the effects of BTB on male sexual competence. Different doses of BTB made from Sri Lankan high grown dust grade no 1 tea (84, 167 and 501 mg/ml) or water were orally administered to separate groups of rats (n=9 per group) and 3h later their sexual behaviour were monitored (for 15 min) using receptive females. The overall results showed that BTB possesses marked aphrodisiac activity (in terms of prolongation of latency of ejaculation shortening of mount- and intromission latencies and elevation of serum testosterone level). The aphrodisiac action had a rapid onset and appears to be mediated via inhibition of anxiety and elevation of serum testosterone level. Further, this aphrodisiac action was not associated with impairment of other sexual parameters like libido, sexual motivation, sexual arousal, sexual vigour or penile erection. BTB was also nontoxic (in terms of overt signs, liver and renal toxicity). It is concluded that BTB can function as a quick acting, safe, oral aphrodisiac which may also be useful in certain forms of sexual inadequacies such as premature ejaculation and impaired libido and other sexual functions.